2016
DOI: 10.1021/acs.joc.6b02708
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed [3 + 2] Annulation of Cyclic N-Acyl Ketimines with Activated Olefins: Anticancer Activity of Spiroisoindolinones

Abstract: The rhodium(III)-catalyzed redox-neutral coupling reaction of N-acyl ketimines generated in situ from 3-hydroxyisoindolinones with various activated olefins is described. This approach leads to the synthesis of bioactive spiroisoindolinone derivatives in moderate to high yields. In the case of internal olefins such as maleimides, maleates, fumarates, and cinnamates, spiroindanes were obtained by the [3 + 2] annulations reaction. In sharp contrast, acrylates and quinones displayed the β-H elimination followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 58 publications
(15 reference statements)
1
41
0
Order By: Relevance
“…In 2017, Kim's group reported a rhodium(III)‐catalyzed [3+2] annulation of N ‐acyl ketimine derivatives with maleimides . This method leads to the formation of spiroisoindolinone derivatives in good to excellent yields in a highly stereoselective manner.…”
Section: Annulation Of Aromatics With Maleimidesmentioning
confidence: 99%
“…In 2017, Kim's group reported a rhodium(III)‐catalyzed [3+2] annulation of N ‐acyl ketimine derivatives with maleimides . This method leads to the formation of spiroisoindolinone derivatives in good to excellent yields in a highly stereoselective manner.…”
Section: Annulation Of Aromatics With Maleimidesmentioning
confidence: 99%
“…Cyclic imines are of prime importance as they could lead to the formation of spirocompounds via a [3 + 2] annulation reaction. In 2016, Kim described The Rh(III)-catalyzed redox-neutral coupling process of N-acyl ketimines generated in situ from 3-hydroxyisoindolinones with a wide range of activated olefins (Scheme 48) [147]. This approach led to the synthesis of bioactive spiroisoindolinone derivatives in good yields.…”
Section: Construction Of Spiroheterocyclesmentioning
confidence: 99%
“…(3)]. [117] It was found that olefins of maleimides, maleates, fumarates, and cinnamates led to the formation of spiroindane products via the [3+ +2] annulation, while acrylates and quinones furnished unsaturated spiroindene products resulting from b-H elimination ands ubsequent Prins-typecyclization.…”
Section: With Cyclic Aryl Ketiminesmentioning
confidence: 99%
“…Very recently, a rhodium‐catalyzed [3+2] annulation of N ‐acyl ketimines with various activated olefins is described by the Kim group [Eq. (3)] . It was found that olefins of maleimides, maleates, fumarates, and cinnamates led to the formation of spiroindane products via the [3+2] annulation, while acrylates and quinones furnished unsaturated spiroindene products resulting from β‐H elimination and subsequent Prins‐type cyclization.…”
Section: N‐substituted Quaternary Centersmentioning
confidence: 99%